Evaluating ex vivo toll-like receptor agonist response as a potential biomarker in equine gastric ulcer syndrome - Gustavo Ferlini Agne; Daniel Thomas Barratt; Bridget Eileen May; Mark R. Hutchinson; Joshua Holmes; Catherine Steel; Olivier Simon; Samuel Greig Evans; Andrew A. Somogyi; Benjamin W. Sykes; Samantha Franklin (The Veterinary Journal, 2026)

Microbial succession and spoilage dynamics revealed by multi-omics in Norway lobster (Nephrops norvegicus) during ice storage - Ahmed Elsheshtawy; Benjamin G.J. Clokie; Sasha Saugh; Karen D. Adler; Slawomir M. Michniewski; Simon MacKenzie; Martha R.J. Clokie; Thomas Sicheritz-Pontén; Amaya Albalat (Food Microbiology, 2026)

Examining fish diversity across an inverse salinity gradient using eDNA - Kirsty E. Richards; Simon Jarman; Benjamin J. Saunders; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2026)

Sulfate-driven phosphorus recycling and the collapse of lacustrine ecological diversity in the mid-Triassic - Wei Shi; Chao Li; Rukai Zhu; Benjamin J.W. Mills; Chunlian Wang; Jingwei Cui; Thomas J. Algeo; Mingtao Li; Mingcai Hou; Simon W. Poulton (Earth and Planetary Science Letters, 2026)

Effect of temperature (77–1473 K) on H2O and CO2 in opal: An in situ mid- and near-infrared (MIR-NIR) spectroscopy study - Alessandra Conte; Giancarlo Della Ventura; Benjamin Rondeau; Boris Chauviré; Simon Gouzy; Mariangela Cestelli Guidi; Martina Romani; Federico Lucci (Icarus, 2026)

A molybdenum isotope perspective on oceanic palaeoredox conditions during the Cryogenian non-Snowball interlude - Jin Li; Xiang-kun Zhu; Fred T. Bowyer; Benjamin J.W. Mills; Xi Peng; Bin Yan; Simon W. Poulton (Global and Planetary Change, 2026)

Using life-history information to identify management priorities within an emergent multi-species grey mullet fishery - Calum J. Pritchard; Ayşegül Tuğçe Han; Andrew Macleod; Rachel M. Turnbull; Jamie Small; Sarah Birchenough; Simon Pengelly; Benjamin J. Ciotti (Fisheries Research, 2026)

Using interactive education materials to empower children to be future consumers of alternative proteins: A randomised active-controlled trial - Aimee E. Pink; Kum Seong Wan; Siti Amelia Juraimi; Mansi Bhatnagar; Jolene Chee; Hui Si Oh; Joseph Simons; Pey Sze Teo; Florence Sheen; Mary F-F Chong; Benjamin P.C. Smith; Anna Fogel (Appetite, 2026)

Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

Can lizards count? Testing numerosity in an Australian skink using spontaneous quantity discrimination - K.N. Rachel Wong; Simon Jeni; Benjamin J. Ashton; Culum Brown; Martin J. Whiting (Animal Behaviour, 2026)

How do nutrient supply and reduced tillage influence weed flora and its impact on grain maize growth under organic farming? - Christophe Lacroix; Bruno Huyghebaert; Simon Sail; Morgan Abras; Benjamin Dumont (European Journal of Agronomy, 2026)

The influence of abiotic (snow fences) and biotic (hedgerows) vertical structures on natural plant recolonization in subarctic mine site reclamation - Benjamin F. Budzey; Simon M. Landhäusser; Katherine J. Stewart (Ecological Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Deciphering phosphorus dynamics in impacted river systems using phosphate oxygen and lead isotope analysis - Daren C. Gooddy; Andrew M. Tye; Andrew C. Smith; Simon R. Chenery; Benjamin JW. Surridge (Applied Geochemistry, 2026)

Whole‐Genome‐Sequencing Reveals Demographic History and Patterns of Parallel Adaptive Evolution in Indo‐Pacific Bottlenose Dolphins ( Tursiops aduncus ) Across Coastal Australian Seascapes - Svenja M. Marfurt; Adrien Tran Lu Y; Benjamin Dauphin; Manuela R. Bizzozzero; Masaomi Hatakeyama; Delphine B. H. Chabanne; Simon J. Allen; Felix Smith; Guido J. Parra; Michael Krützen (Molecular Ecology, 2026)
Understanding how demographic dynamics interact with environmental heterogeneity is central to explaining patterns of genomic variation in the marine realm. Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) occur along most of the Australian coastline, from tropical to temperate waters, encompassing pronounced differences in temperature, salinity, chlorophyll‐a concentration and ocean currents. Using whole‐genome sequencing of individuals covering this range, we examined population genetic structure and adaptive divergence at a continental scale. Genome‐wide variation mirrored geographic patterns, consistent with a common origin in the north, followed by two independent stepping‐stone‐like colonization patterns along the eastern and the western coastlines from north to south. In contrast, putatively adaptive loci clustered individuals by tropical waters regardless of geographic distance, indicating strong parallel adaptation in tropical habitats. Candidate loci were enriched for functions related to metabolism and ion transport, with some mapping to genes with regulatory functions. Additional signals potentially suggest involvement of neuronal pathways, consistent with adaptation in a highly social and cognitively advanced marine mammal. Our results highlight the complex interplay between demographic history and selection and suggest tropical–temperate, potentially ecotype‐like differentiation across Australian waters. In the face of accelerating climate change, recognizing such adaptive structuring is critical for preserving evolutionary potential. Incorporating adaptive genomic information into conservation planning, alongside neutral genetic data, will be essential for anticipating population responses to future environmental change and for identifying biologically meaningful conservation units.

Preservation of organic molecules in silica and sepiolite clay under UV radiation - Simon Gouzy; Fabien Stalport; Benjamin Rondeau; Vassilissa Vinogradoff; Elisabeth Lapp; Florian Massuyeau; Maxime Pineau; Rachel Gonthier; Hervé Cottin; John Carter (Icarus, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Spatial resilience and population replacement in Europe during MIS 3: a comparative study of Neanderthals and H. sapiens - Ariane Burke; Emma Pomeroy; Timothée Poisot; Benjamin Albouy; Simon Paquin (Quaternary Science Reviews, 2026)

Comparative Biogeography of Benthic and Mid‐Water Coastal Fish Communities of the Galapagos: Stereo‐ BRUVs Surveys Support the Use of Bioregions for Management - Etienne Rastoin‐Laplane; Simon James McKinley; Pelayo Salinas‐de‐León; David Acuña‐Marrero; Jordan Goetze; Benjamin J. Saunders; Hannah Ashe; Megan Cundy; Euan S. Harvey (Journal of Biogeography, 2026)
Aim Biogeographical frameworks inform effective marine spatial planning, assessing ecological patterns across taxa and environments. In the Galapagos Archipelago, benthic bioregions guided marine reserve zoning, yet their representation of the mid‐water environment remains unassessed. Our study aimed to strengthen the understanding of patterns in marine biogeography in Galapagos by assessing whether the currently accepted benthic bioregions also represent mid‐water reef fish communities. Location Galapagos Archipelago. Taxon Marine fish species. Methods We used baited remote underwater stereo‐video systems to conduct archipelago‐wide surveys of benthic and mid‐water fish communities. Locations were sampled during the cold and warm seasons, yielding 598 deployments which were analysed to compare multivariate patterns between bioregions and environments. Results Bioregion partitioning based on benthic fish community data was more distinct than in previous studies with the Far‐North, North, Centre‐Southeast and West bioregions displaying significantly different community compositions. The main Galapagos bioregions displayed less distinct coastal mid‐water fish communities suggesting three subdivisions may be more representative, namely the Far‐North, West and the Centre‐Southeast plus North combined. When compared with benthic communities, mid‐water communities displayed higher heterogeneity, lower species richness and were dominated by species with extensive distribution ranges. Main Conclusions Our study builds upon previous biogeographic studies in the Galapagos Islands by considering previous limitations and assessing both benthic and mid‐water environments. Our results support the currently accepted bioregion scheme but suggest that the coastal mid‐water environment could be divided into three, not four bioregions. Mid‐water stereo‐BRUVs represent a useful tool to study mid‐water biogeographical patterns, and we recommend their application in other regions of the world to improve our understanding of biogeography in this understudied environment.

A mid‐Proterozoic coupled Sr and Li isotope excursion and its potential connection to enhanced weathering and ocean oxygenation at 1.57 Ga - Xi Chen; Ying Zhou; Simon W. Poulton; Fred T. Bowyer; Colin Mettam; Shihong Zhang; Maoyan Zhu; Da Li; Philip A.E. Pogge von Strandmann; Benjamin J.W. Mills; Graham A. Shields (Earth and Planetary Science Letters, 2026)

How to maintain soil fertility in stockless organic farming: Research concepts and insights from the first crop rotation of a long-term field experiment - Morten Möller; Miriam Athmann; Simon Dreßen; Tobias Karl David Weber; Benjamin Ruch; Christian Bruns (Organic Agriculture, 2026)
With the increase of organic agriculture throughout Europe, there is also an increase of stockless organic farms. On mixed farms, growth of perennial legume-grass mixtures as well as farmyard manure are important contributors to soil fertility and play a key role for nutrient management. On stockless farms, such crops have no direct economic use and their cultivation is therefore questionable, which poses challenges for maintaining nutrient balance and soil fertility. Disentangling physical, chemical, and biological long-term impacts on soil fertility and consequently on crop yield and quality requires long-term research. In 2017, a long-term field experiment was established in Hesse, Germany, in which three stockless organic farm types differing in crop rotation, each combined with three different fertilization treatments, are compared to a traditional mixed farm type with three livestock density levels. The results of the first crop rotation show that the Mixed Farm type achieved more synchronized nutrient input and output with increasing livestock density. Stockless farm types showed deficits, especially in P and K balances, unless compensated by organic fertilizers from external sources. The application of compost and grass-clover silage prepared from on site fertility-building leys resulted in significant increases in soil organic carbon. Significant correlations between soil organic carbon and crop yields in stockless farm types using compost emphasize the importance of soil organic carbon content for productivity in organic farming systems. In contrast, at least in this first rotation, treatments with lower organic matter inputs benefited from high site fertility and showed no yield declines.

Examining Marine Assemblages Across an Inverse Salinity Gradient - Kirsty E. Richards; Simon Jarman; Benjamin J. Saunders; Shaun Wilson; Euan S. Harvey (Molecular Ecology, 2026)
Salinity gradients and fluctuations can create a natural ecological filter, with few species tolerating salinity above 50 practical salinity units (PSUs). We investigated how an inverse salinity gradient affected marine community diversity and composition in Shark Bay, a remote hypersaline coastal embayment in Western Australia. We used 16S(fish), 18S and 16S(Bacteria) eDNA metabarcoding assays to analyse genetic sequences collected from 220 surface water samples and 216 benthic roller samples. The 44 survey sites encompassed a salinity gradient of 40.1 PSU in the Eastern Gulf to 76.0 PSU in Hamelin Pool. 24,011,345 eDNA sequencing reads were detected from 5575 operational taxonomic units (OTUs). The number of Families and OTUs, and OTUs within key Phyla, all decreased with increasing salinity, the most dramatic changes occurring over a narrow salinity range (50–60 PSU). However, the relative proportion of Families from each Phyla contributing to the total assemblage within each salinity range remained relatively stable. Key processes may therefore be maintained across the salinity gradient, although redundancy and resilience are compromised as diversity declines and the taxonomic composition of the communities changes. Although primary producers such as cyanobacteria, seagrass and the bivalve mollusc Fragum spp. were under‐represented within our data set, this may be due to a limitation of the eDNA methods used rather than their absence within the ecosystem. Even with these limitations, eDNA has proven a useful tool for examining the whole marine assemblage across an inverse salinity gradient in a remote area at a broad taxonomic level.

Forest Heterogeneity by Chain Saw: How Between‐Patch Variation in Old Growth Attributes Changes the Metacommunities of Beetles - Oliver Mitesser; Marc W. Cadotte; Akira S. Mori; Fons van der Plas; Anne Chao; Julia Rothacher; Claus Bässler; Mirjana Bevanda; Peter H. W. Biedermann; Pia Bradler; Antonio Castañeda‐Gómez; Orsi Decker; et al. (Ecology Letters, 2026)
Metacommunity theory has expanded our understanding of how spatial dynamics and local interactions influence species communities. Different assembly archetypes, reflecting different roles of species differences, habitat differences, and dispersal have been described, but we lack empirical studies specifically in terrestrial habitats testing which archetype is most important. In a replicated design, we experimentally enhanced structural between‐patch heterogeneity in homogeneous production forests and developed a statistical framework controlling for sample incompleteness to detect different metacommunity processes. Meta‐analyses on > 100 K individuals of > 1.3 K beetle species showed an increase of ~60 species in heterogenized forests at γ‐level promoted by increasing α‐diversity consistent with the mass‐effect and an increase of β‐diversity by ~10% supporting species‐sorting . Additionally, we tested β‐deviations from random assembly as a proxy of neutral processes . Findings indicate that enhancing structural heterogeneity can shift forests from patch‐dynamics dominance towards mass‐effect and species‐sorting , offering a promising pathway to restore biodiversity in managed landscapes.

Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Environmental consequences of genetic improvement of growth and fillet yield in gilthead seabream: A life cycle assessment from breeding to plate - Sophie De Montmorillon; Simon Pouil; Marc Vandeputte; Jean-Sébastien Bruant; Jérôme Bugeon; Ivonne Acosta-Alba; Cédric Pincent; Benjamin Quittet; Mathieu Besson; Joël Aubin; Pierrick Haffray (Aquaculture, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Investigations into highly stable GNSS ground and space clocks using a network of globally distributed H-maser stations - Jari Simon Widczisk; Benjamin Männel; Jens Wickert (GPS Solutions, 2026)
Modeling station and satellite clocks in the GNSS analysis in order to reduce existing correlations requires a high level of stability for the corresponding clocks. In this contribution, we provide a comprehensive and up-to-date status regarding the stability of on-board clocks of GPS, GLONASS, and Galileo satellites, as well as hydrogen maser stations within the International GNSS Service network. We use exemplary events of irregularities to show which factors need to be taken into account when analyzing a longer period of GNSS clocks. Based on epoch-wise clock biases estimated for different sampling rates (5 min / 30 s) in a daily network solution from May 2023 to April 2024, various stability analyses are carried out. About 60 of the 80 hydrogen maser stations distributed worldwide show a high stability with an average daily standard deviation of less than 75 picoseconds. For the satellite clocks the stability depends mainly on the atomic clock type and the age of the satellite block. In a further stability analysis, the 5-min clock estimates are subjected to a linear regression analysis with different interval lengths. The clock estimates of the younger satellite generations (GPS IIF, GPS IIIA, Galileo FOC) and the highly stable hydrogen maser stations can be well characterized by linear representations; assuming 10 mm as a threshold for the mean regression fit RMS, the maximum interval lengths are two and eight hours, respectively.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

The social welfare value of the global food system - Simon Dietz; Benjamin Bodirsky; Michael Crawford; Ravi Kanbur; Debbora Leip; Steven Lord; Hermann Lotze-Campen; Alexander Popp (Ecological Economics, 2026)

Hydrothermal co-enrichment of Au, As, Co, and Cu in orogenic deposits: insights from the Pohjanmaa belt - Andressa de Araujo Silva; Simon Hector; Clifford Patten; Aratz Beranoaguirre; Elisabeth Eiche; Benjamin F. Walter; Jochen Kolb (Mineralium Deposita, 2026)
The Huhta Au and Jouhineva Au-Co-Cu-Ag deposits lie ~ 3 km apart in the Pohjanmaa Belt, western Finland, in Paleoproterozoic metavolcano-sedimentary host rocks. Both deposits are spatially and genetically related to the Sievi shear zone but have different metal endowments. The main regional structural grain is characterized by D 2 -D 3 fold interference and NW-SE to NNW-SSE-trending D 3 shear zones. Huhta hosts auriferous D 3 quartz-arsenopyrite veins, while Jouhineva contains auriferous, Co-bearing D 3 arsenopyrite-actinolite-quartz, and D 4 quartz-chalcopyrite veins with native gold. Uranium–Pb titanite ages of ~ 1830 Ma in D 3 veins and alteration zones align with regional metamorphism. Gold mineralization postdates the intrusion of the nearby Rautio Batholith and peak metamorphism by ~ 50 m.y. The auriferous D 4 veins formed during progressive terrane exhumation, likely at ~ 1805 Ma, contemporaneously with orogenic gold deposits in greenstone belts further south. Accretionary and collisional tectonics during the Svecobaltic orogeny represent the regional control for deformation and hydrothermal activity. Lack of precision in the titanite U–Pb data does not allow resolution between the absolute timing of orogenic mineralization at Jouhineva and Huhta, however, structures, veins, and alteration assemblages are similar, except for cobaltite in Jouhineva. This indicates contemporaneous formation of typical and atypical orogenic gold deposits in the region. Cobalt enrichment restricted to Jouhineva may be explained by different pH and/or fO 2 during fluid-rock interaction or localized and compartmentalized fluid migration of different fluids in the Sievi shear zone system. Cobalt and Cu enrichment in Jouhineva are genetically and temporally unrelated, with the Cu-Au event being ~ 25 m.y. younger.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Circular food systems in Kenya: Exploring the role of livestock - Dagmar J.M. Braamhaar; Benjamin van Selm; Jan van der Lee; Simon J. Oosting (Agricultural Systems, 2026)

Thermal infrared characterization of spatially unresolved resident space objects: Prospects from analytical two-component modeling - Stephen Catsamas; Sarah Caddy; Michele Trenti; Benjamin Metha; Simon Barraclough; Robert Mearns; Airlie Chapman; Rachel Webster (Advances in Space Research, 2026)

Underwater Behavior of Southern Hemisphere Humpback Whales ( Megaptera novaeangliae ) Feeding in Super‐Groups, From Video Footage - Simon H. Elwen; Rebecca Hannén; Steve Benjamin; Claudio Velasquez Rojas; Rachel Probert; Tess Gridley (Marine Mammal Science, 2026)
Large “super‐groups” of feeding humpback whales ( Megaptera novaeangliae ) have occurred regularly off the West Coast of South Africa since ca. 2011, but little is known about their feeding behavior. We used opportunistic underwater video footage to investigate near‐surface lunge feeding behavior, group coordination, and the use of pectoral fins in feeding. We analyzed 113 min of underwater video footage collected over 6 days. Whales passed through the frame on 623 occasions and were seen actively lunging on 182 occasions. No lateralization or coordinated foraging was observed. Gape cycles were short (mean mouth opening phase: 2.38 s and mouth closing: 1.69 s) with buccal pouch draining lasting the longest (15.61 s) and being a mostly passive action. The whales often surfaced while the pouch still contained water. Lunges and draining took place in all directions but mostly at ascending and even near vertical angles. Active flipper movements were observed during 81% of feeding lunges, providing further evidence that these uniquely large appendages are used hydrodynamically when feeding and may also play a role in prey herding. Disruption of feeding by diver presence was low. This study provides novel insight into the feeding behavior of Southern Hemisphere humpback whale super‐groups, and potential human‐whale interactions.

A Herculean task: classical simulation of quantum computers - Xiaosi Xu; Simon Benjamin; Jianxin Chen; Jinzhao Sun; Xiao Yuan; Pan Zhang (Science Bulletin, 2025)

Residual barley proteins in brewers' spent grains: Quantitative composition and implications for food ingredient applications - Simon Gregersen Echers; Rasmus Kranold Mikkelsen; Naim Abdul-Khalek; Lucas Sales Queiroz; Timothy John Hobley; Benjamin L. Schulz; Michael Toft Overgaard; Charlotte Jacobsen; Betül Yesiltas (Innovative Food Science & Emerging Technologies, 2025)

Insight on the global water distribution in opal considering its bi-component nature - Simon Gouzy; Boris Chauviré; Benjamin Rondeau; Vassilissa Vinogradoff; John Carter (Physics and Chemistry of Minerals, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Characteristics and outcomes of patients with infective native aortic aneurysm or vascular graft and endograft infection - Lucas Lalevée; Malikov Sergueï; Elodie Jeanbert; Maïa Simon; Amandine Luc; Nicla Settembre; Sandrine Hénard; Emmanuel Novy; Philippe Guerci; Benjamin Lefèvre (Infectious Diseases, 2025)

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Organic carbon, sea level and carbonate weathering controls on marine carbon isotope perturbations across the Hirnantian glaciation - Jiaqiang Zhang; Zhen Qiu; Wenjiao Xiao; Paul B. Wignall; Weiliang Kong; Benjamin J.W. Mills; Yijun Xiong; Simon W. Poulton (Earth and Planetary Science Letters, 2025)

Testing the effectiveness of education to increase acceptance of alternative proteins in children: A randomised control trial - Florence Sheen; Siti Amelia Juraimi; Wan Kum Seong; Joseph Simons; Pey Sze Teo; Myat Min; Petrus Bonang; Kristabel Khoo; Benjamin P.C. Smith; Mary F-F. Chong; Anna Fogel; Aimee E. Pink (Appetite, 2025)

A novel UNet-SegNet and vision transformer architectures for efficient segmentation and classification in medical imaging - Simon Tongbram; Benjamin A. Shimray; Loitongbam Surajkumar Singh (Physical and Engineering Sciences in Medicine, 2025)

Duration of isobaric heating and slab rollback in the Aegean extensional province, Eastern Mediterranean: Evidence from garnet diffusion modelling - Alexandre Peillod; Benjamin Hess; Evangelos Moulas; Simon Hector; Clifford G.C. Patten; Aratz Beranoaguirre; Uwe Ring (Earth and Planetary Science Letters, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

From Presence‐Only to Abundance Species Distribution Models Using Transfer Learning - Benjamin Bourel; Alexis Joly; Maximilien Servajean; Simon Bettinger; José Antonio Sanabria‐Fernández; David Mouillot (Ecology Letters, 2025)
Species Distribution Models based on Convolutional Neural Networks (CNN‐SDMs) have recently emerged, demonstrating greater effectiveness than traditional SDMs in several contexts. A limited number of studies, however, have focused on species abundance patterns, as the datasets available for this purpose are generally too small to effectively learn a deep learning model with millions of parameters. Our study demonstrated that CNN‐SDMs can circumvent the small sample size of species abundance datasets through the combined use of a large presence‐only species dataset and transfer learning to significantly improve the performance of abundance‐based CNN‐SDMs. Applied to Mediterranean coastal fishes, our approach significantly improves the abundance prediction performance of CNN‐SDMs, with average gains of 35% (D‐squared regression score). This allows CNN‐SDMs to perform better than classical SDMs in abundance prediction, with average gains of 10%. These gains are stemming from enhanced abundance predictions for rare species and where widespread species are locally rare.

MAS—A mission analysis software for collision risk quantification and impact assessment of rule-based decision-making for collision avoidance - Simon Burgis; Hans Rübberdt; Christoph Gaedigk; Louis Keuper; Georgette Naufal; Jonko Paetzold; Xanthi Oikonomidou; Benjamin Bastida Virgili (Journal of Space Safety Engineering, 2025)

Changes in behaviour and serotonergic system of Atlantic salmon (Salmo salar) fry related to different levels of black soldier fly larvae meal inclusion in the diet: Exploring the use of nutritional enrichment for its use as positive welfare in aquaculture - Mauro Chivite-Alcalde; Monica Betancor; Benjamin G J Clokie; Ahmed Elsheshtawy; Emma McDonald; Carlos Ramírez-Rodríguez; Miha Pipan; Simon A. MacKenzie; Sonia Rey Planellas (Applied Animal Behaviour Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Adaptive capacities of inland fisheries facing anthropogenic pressures - Gretchen L. Stokes; Samuel J. Smidt; Emily L. Tucker; Matteo Cleary; Simon Funge-Smith; John Valbo‐Jørgensen; Benjamin S. Lowe; Abigail J. Lynch (Global Environmental Change, 2025)

Habitability for a connected, unequal and changing world - Harald Sterly; Marion Borderon; Patrick Sakdapolrak; Neil Adger; Ayansina Ayanlade; Alassane Bah; Julia Blocher; Suzy Blondin; Sidy Boly; Timothée Brochier; Loïc Brüning; Simon Bunchuay-Peth; et al. (Global Environmental Change, 2025)

Drought acclimation of beech seedlings depends largely on their rooting patterns and less on the fungal communities in soils - Jasmin Danzberger; Kyohsuke Hikino; Simon M. Landhäusser; Benjamin D. Hesse; Sophie Meyer; Franz Buegger; Fabian Weikl; Thorsten E. E. Grams; Karin Pritsch (Plant and Soil, 2025)
Aims The composition of soil fungal communities is known to impact tree performance. However, fungal communities differ among soils with different precipitation histories and may change during drought. This study aimed to determine the influence of soil origin and associated climate adaptation of fungal communities on European beech seedlings’ drought responses. Methods Seedlings were established from the same seed source and grown in three soils with different precipitation histories but similar water retention properties. One year after establishment, half of the seedlings were exposed to a two-month drought with predawn leaf water potentials of about –1.5 MPa, the other half remained well-watered (control). Before and during the drought, soil and root fungal community composition, root architecture, seedling growth, carbon allocation and leaf physiology were determined. Results The drought effect on the fungal community composition was the lowest in dry region soils, suggesting a natural adaptation of the fungal communities to dry environments. Nevertheless, contrary to our expectations, the seedlings grown in dry region soils with respective adapted fungal communities were most affected by drought. This was evidenced by a lower predawn water potential, probably due to shorter root systems with higher root branching compared to those grown in moist region soils where a greater taproot length was observed. Conclusion Beech seedlings´ drought responses depend largely on their different rooting patterns and less on the soil fungal communities that are adapted to long-term precipitation conditions. Yet, microbial effects cannot be excluded. Future research should focus more on the role of specific microbial species on plant root growth and drought responses.

Morphological analyses support taxonomic updates in Brazilian species of Stylosanthes Sw. (Papilionoideae, Leguminosae) - Danilo Soares Gissi; Benjamin M. Torke; Marcelo Fragomeni Simon; Mario Tomazello-Filho; Ana Paula Fortuna-Perez (Brazilian Journal of Botany, 2024)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

Life in the margins: the effect of immersion/emersion and tidal cycle on the North Atlantic limpet Patella vulgata protein synthesis rates - Ignacio A. Cienfuegos; Benjamin J. Ciotti; Richard A. Billington; Paul A. Sutton; Simon G. Lamarre; Keiron P. P. Fraser (Journal of Comparative Physiology B, 2024)

Restorative function of offshore longline mussel farms with ecological benefits for commercial crustacean species - Thomas Stamp; Simon J. Pittman; Luke A. Holmes; Adam Rees; Benjamin J. Ciotti; Harry Thatcher; Peter Davies; Alice Hall; Georgia Wells; Anna Olczak; Emma V. Sheehan (Science of The Total Environment, 2024)

The diversity of researchers’ roles in sustainability science: the influence of project characteristics - Guillaume Pajot; Benjamin Bergerot; Simon Dufour; Valérie Viaud; Christophe Cudennec; Gérard Gruau; Tassadit Bouadi; Cyrille Harpet; Jean-Raynald de Dreuzy; Nathalie Hervé-Fournereau; Véronique Van Tilbeurgh; Luc Aquilina (Sustainability Science, 2024)

Ceftriaxone reverses diet-induced deficits in goal-directed control - Benjamin-Israel Moke; Megan L. Shipman; Simon Lui; Laura Corbit (Psychopharmacology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mutant PTPMT1 disrupts cardiolipin metabolism and mitochondrial bioenergetics leading to a neurodevelopmental syndrome - Micol Falabella; Chiara Pizzamiglio; Luis Carlos Tabara; Benjamin Munro; Mohamed S. Abdel-Hamid; Ece Sonmezler; William L. Macken; Shanti Lu; Lisa Tilokani; Padraig J. Flannery; Simon A.S. Pope; Simon J.R. Heales; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

The development of an interactive platform to educate children on alternative proteins - Aimee E. Pink; Siti Amelia Juraimi; Arunika Pillay; Liang Ze Wong; Joseph Simons; Florence Sheen; Anna Fogel; Mary F-F Chong; Benjamin P.C. Smith; Kristabel Khoo; Petrus Bonang; Myat Min (Appetite, 2024)

Evaluating the impact of climate change and millennial variability on the last Neanderthal populations in Europe (Marine Isotope Stage 3) - Benjamin Albouy; Simon Paquin; Julien Riel-Salvatore; Masa Kageyama; Mathieu Vrac; Ariane Burke (Quaternary Science Reviews, 2024)

Variability in flood frequency in sub-Saharan Africa: The role of large-scale climate modes of variability and their future impacts - Job Ekolu; Bastien Dieppois; Yves Tramblay; Gabriele Villarini; Louise J. Slater; Gil Mahé; Jean-Emmanuel Paturel; Jonathan M. Eden; Simon Moulds; Moussa Sidibe; Pierre Camberlin; Benjamin Pohl; et al. (Journal of Hydrology, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

New sensitive tools to characterize meta-metabolome response to short- and long-term cobalt exposure in dynamic river biofilm communities - Simon Colas; Benjamin Marie; Soizic Morin; Mathieu Milhe-Poutingon; Pierre Foucault; Siann Chalvin; Clémentine Gelber; Patrick Baldoni-Andrey; Nicholas Gurieff; Claude Fortin; Séverine Le Faucheur (Science of The Total Environment, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Sensitivity of air quality to vehicle ammonia emissions in the United States - Claudia Toro; Darrell Sonntag; Jesse Bash; Guy Burke; Benjamin N. Murphy; Karl M. Seltzer; Heather Simon; Mark W. Shephard; Karen E. Cady-Pereira (Atmospheric Environment, 2024)

Meta-metabolomic responses of river biofilms to cobalt exposure and use of dose-response model trends as an indicator of effects - Simon Colas; Benjamin Marie; Mathieu Milhe-Poutingon; Marie-Claire Lot; Amiel Boullemant; Claude Fortin; Séverine Le Faucheur (Journal of Hazardous Materials, 2024)

Anatomically modern human dispersals into Europe during MIS 3: Climate stability, paleogeography and habitat suitability - Simon Paquin; Benjamin Albouy; Masa Kageyama; Mathieu Vrac; Ariane Burke (Quaternary Science Reviews, 2024)

Intercomparison of surface velocimetry techniques for drone-based marine current characterization - Iain Fairley; Nicholas King; Jason McIlvenny; Matthew Lewis; Simon Neill; Benjamin J. Williamson; Ian Masters; Dominic E. Reeve (Estuarine, Coastal and Shelf Science, 2024)

Exploring the impact of thermal delousing on gill health and microbiome dynamics in farmed Atlantic Salmon - Ahmed Elsheshtawy; Benjamin Gregory James Clokie; Amaya Albalat; Are Nylund; Birgit Lilletveit Kvåle; Linda Andersen; Lindsey Jane Moore; Simon MacKenzie (Aquaculture, 2024)

Hill–Chao numbers allow decomposing gamma multifunctionality into alpha and beta components - Anne Chao; Chun‐Huo Chiu; Kai‐Hsiang Hu; Fons van der Plas; Marc W. Cadotte; Oliver Mitesser; Simon Thorn; Akira S. Mori; Michael Scherer‐Lorenzen; Nico Eisenhauer; Claus Bässler; Benjamin M. Delory; et al. (Ecology Letters, 2024)
Biodiversity–ecosystem functioning (BEF) research has provided strong evidence and mechanistic underpinnings to support positive effects of biodiversity on ecosystem functioning, from single to multiple functions. This research has provided knowledge gained mainly at the local alpha scale (i.e. within ecosystems), but the increasing homogenization of landscapes in the Anthropocene has raised the potential that declining biodiversity at the beta (across ecosystems) and gamma scales is likely to also impact ecosystem functioning. Drawing on biodiversity theory, we propose a new statistical framework based on Hill–Chao numbers. The framework allows decomposition of multifunctionality at gamma scales into alpha and beta components, a critical but hitherto missing tool in BEF research; it also allows weighting of individual ecosystem functions. Through the proposed decomposition, new BEF results for beta and gamma scales are discovered. Our novel approach is applicable across ecosystems and connects local‐ and landscape‐scale BEF assessments from experiments to natural settings.

Intervention: The invisible labor of climate change adaptation - Leigh Johnson; Michael Mikulewicz; Patrick Bigger; Ritodhi Chakraborty; Abby Cunniff; P. Joshua Griffin; Vincent Guermond; Nicole Lambrou; Megan Mills-Novoa; Benjamin Neimark; Sara Nelson; Costanza Rampini; et al. (Global Environmental Change, 2023)

The geophysical toolbox applied to forest ecosystems – A review - Bertille Loiseau; Simon D. Carrière; Damien Jougnot; Kamini Singha; Benjamin Mary; Nicolas Delpierre; Roger Guérin; Nicolas K. Martin-StPaul (Science of The Total Environment, 2023)

Fluctuations of Galapagos mid-water and benthic reef fish populations during the 2015–16 ENSO - Etienne Rastoin-Laplane; Pelayo Salinas-de-León; Jordan S. Goetze; Benjamin J. Saunders; Simon J. McKinley; Courtney Norris; Corinna Gosby; Andrea Mattingly; Rodrigo Garcia; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2023)

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

Consumption of plant-based meat alternatives by regular consumers and their motivations to sustain long-term intake. - Siti Amelia Juraimi; Florence Sheen; Benjamin Smith; Joseph Simons; Jennifer Gatzemeier; Rochelle Embling; Aimee E. Pink (Appetite, 2023)

How do primates decide where to feed? Insights from wild western gorillas - Benjamin Robira; Simon Benhamou; Erlich Obeki Bayanga; Thomas Breuer; Shelly Masi (Animal Behaviour, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Vegetation productivity drives soil mineral associated organic matter formation and the relative contribution of sorption capacity across climates. - Brian Morra; Cody Reed; Simon R. Poulson; Benjamin W. Sullivan (Rhizosphere, 2023)

Experimental upscaling analyses for a surfactant-enhanced in-situ chemical oxidation (S-ISCO) remediation design - Benjamin M. Herzog; Simon M. Kleinknecht; Claus P. Haslauer; Norbert Klaas (Journal of Contaminant Hydrology, 2023)

Heterogeneous sulfide reoxidation buffered oxygen release in the Ediacaran Shuram ocean - Wei Shi; Benjamin J.W. Mills; Thomas J. Algeo; Simon W. Poulton; Robert J. Newton; Matthew S. Dodd; Zihu Zhang; Lei Zheng; Tianchen He; Mingcai Hou; Chao Li (Geochimica et Cosmochimica Acta, 2023)

Altered ovarian transcriptome is linked to early mortality and abnormalities in zebrafish embryos after maternal exposure to gamma irradiation - Noëmie Guirandy; Olivier Armant; Sandrine Frelon; Fabien Pierron; Benjamin Geffroy; Guillemine Daffe; Camille Houdelet; Patrice Gonzalez; Olivier Simon (Aquatic Toxicology, 2023)

Stone artefacts on the seabed at a submerged freshwater spring confirm a drowned cultural landscape in Murujuga, Western Australia - Jonathan Benjamin; Michael O'Leary; John McCarthy; Wendy Reynen; Chelsea Wiseman; Jerem Leach; Simon Bobeldyk; Justine Buchler; Philippe Kermeen; Michelle Langley; Adam Black; Hiro Yoshida; et al. (Quaternary Science Reviews, 2023)

Ex Vivo Immunomodulatory Effects of Lactobacillus-, Lacticaseibacillus-, and Bifidobacterium-Containing Synbiotics on Human Peripheral Blood Mononuclear Cells and Monocyte-Derived Dendritic Cells in the Context of Grass Pollen Allergy - Alexander Heldner; Matthew D. Heath; Benjamin Schnautz; Sebastian Kotz; Adam Chaker; Matthias F. Kramer; Constanze A. Jakwerth; Ulrich M. Zissler; Carsten B. Schmidt-Weber; Simon Blank (Probiotics and Antimicrobial Proteins, 2023)
Sensing of the intestinal microbiota by the host immune system is important to induce protective immune responses. Hence, modification of the gut microbiota might be able to prevent or treat allergies, mediated by proinflammatory Th2 immune responses. The aim was to investigate the ex vivo immunomodulatory effects of the synbiotics Pollagen® and Kallergen®, containing the probiotic bacterial strains Lactobacillus , Lacticaseibacillus and Bifidobacterium , in the context of grass pollen allergy. Peripheral blood mononuclear cells (PBMCs) from grass pollen–allergic patients and healthy controls were stimulated with grass pollen extract (GPE) and synbiotics and Gata3 expression and cytokine secretion analyzed. Monocyte-derived dendritic cells (MoDCs) cells were matured in the presence of GPE and synbiotics, co-cultured with autologous naïve T cells and maturation markers and cytokine secretion analyzed. GPE stimulation of PBMCs from grass pollen–allergic patients resulted in a significant higher production of the Th2 cytokines IL-4, IL-5, IL-9 and IL-13 compared to healthy controls. Gata3 + CD4 + T cell induction was independent of the allergic status. The synbiotics promoted IL-10 and IFN-γ secretion and downregulated the GPE-induced Th2-like phenotype. Co-culturing naïve T cells with MoDCs, matured in the presence of GPE and synbiotics, shifted the GPE-induced Th2 cytokine release towards Th1-Th17-promoting conditions in allergic subjects. The investigated synbiotics are effective in downregulating the GPE-induced Th2 immune response in PBMCs from grass pollen–allergic patients as well as in autologous MoDC-T cell stimulation assays. In addition to increased IL-10 release, the data indicates a shift from a Th2- to a more Th1- and Th17-like phenotype.

The characteristics and preservation potential of Hurricane Irma's overwash deposit in southern Florida, USA - Kristen M. Joyse; Nicole S. Khan; Ryan P. Moyer; Kara R. Radabaugh; Isabel Hong; Amanda R. Chappel; Jennifer S. Walker; Christian J. Sanders; Simon E. Engelhart; Robert E. Kopp; Benjamin P. Horton (Marine Geology, 2023)

Upscaling of geological properties in a world-class carbonate geothermal system in France: From core scale to 3D regional reservoir dimensions - Hadrien Thomas; Benjamin Brigaud; Thomas Blaise; Elodie Zordan; Hermann Zeyen; Maxime Catinat; Simon Andrieu; Emmanuel Mouche; Marc Fleury (Geothermics, 2023)

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Functional vulnerability and biogeography of reef fish assemblages in the Galapagos Archipelago - Simon J. McKinley; Benjamin J. Saunders; Etienne Rastoin-Laplane; Pelayo Salinas-de-León; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2023)

The effects of feeding dried browse leaves on rumen ammonia levels, methanogens and protozoa amplification of sheep in the Coastal Savannah of Ghana - Felix Owusu Sarkwa; Tsatsu Adogla-Bessa; Othusitse Ricky Madibela; Wanda Nchidzi Mphinyane; Jeremy Simon Perkins; Eric Cofie Timpong-Jones; Amos Nyarko Gyimah; Benjamin Owusu Otu; Christopher Kofi Tudeka (Tropical Animal Health and Production, 2023)

Goat browse selectivity during conservation grazing in an invaded eastern oak-hickory forest - Wanderson Novais; Benjamin A. Wenner; Jeremy A. Block; Simon C. Power; Elizabeth Porteus; G. Matt Davies (Agroforestry Systems, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

Exploring new antecedent metrics for safety performance in Ghana’s oil and gas industry using partial least squares structural equation modelling (PLS-SEM) - Elvis Kwame Ofori; Simon Appah Aram; Benjamin M. Saalidong; Justice Gyimah; Patrick Niyonzima; Clement Mintah; Isaac Ahakwa (Resources Policy, 2023)

Enhancing the structural diversity between forest patches—A concept and real‐world experiment to study biodiversity, multifunctionality and forest resilience across spatial scales - Jörg Müller; Oliver Mitesser; Marc W. Cadotte; Fons van der Plas; Akira S. Mori; Christian Ammer; Anne Chao; Michael Scherer‐Lorenzen; Petr Baldrian; Claus Bässler; Peter Biedermann; Simone Cesarz; et al. (Global Change Biology, 2023)
Intensification of land use by humans has led to a homogenization of landscapes and decreasing resilience of ecosystems globally due to a loss of biodiversity, including the majority of forests. Biodiversity–ecosystem functioning (BEF) research has provided compelling evidence for a positive effect of biodiversity on ecosystem functions and services at the local (α‐diversity) scale, but we largely lack empirical evidence on how the loss of between‐patch β‐diversity affects biodiversity and multifunctionality at the landscape scale (γ‐diversity). Here, we present a novel concept and experimental framework for elucidating BEF patterns at α‐, β‐, and γ‐scales in real landscapes at a forest management‐relevant scale. We examine this framework using 22 temperate broadleaf production forests, dominated by Fagus sylvatica . In 11 of these forests, we manipulated the structure between forest patches by increasing variation in canopy cover and deadwood. We hypothesized that an increase in landscape heterogeneity would enhance the β‐diversity of different trophic levels, as well as the β‐functionality of various ecosystem functions. We will develop a new statistical framework for BEF studies extending across scales and incorporating biodiversity measures from taxonomic to functional to phylogenetic diversity using Hill numbers. We will further expand the Hill number concept to multifunctionality allowing the decomposition of γ‐multifunctionality into α‐ and β‐components. Combining this analytic framework with our experimental data will allow us to test how an increase in between patch heterogeneity affects biodiversity and multifunctionality across spatial scales and trophic levels to help inform and improve forest resilience under climate change. Such an integrative concept for biodiversity and functionality, including spatial scales and multiple aspects of diversity and multifunctionality as well as physical and environmental structure in forests, will go far beyond the current widely applied approach in forestry to increase resilience of future forests through the manipulation of tree species composition.

Amplified drought trends in Nepal increase the potential for Himalayan wildfires - Binod Pokharel; Shankar Sharma; Jacob Stuivenvolt-Allen; Shih-Yu Simon Wang; Matthew LaPlante; Robert R. Gillies; Sujan Khanal; Michael Wehner; Alan Rhoades; Kalpana Hamal; Benjamin Hatchett; Wan-Yu Liu; et al. (Climatic Change, 2023)

Improvement of mineral nutrition and rooting efficiency of Cannabis sativa L. for in vitro large-scale propagation - Adel Zarei; Benjamin Davis; Biruk A. Feyissa; Elham Tavakouli Dinani; Brigitte Simons (In Vitro Cellular & Developmental Biology - Plant, 2023)

New particle formation at a peri-urban agricultural site - Julien Kammer; Leila Simon; Raluca Ciuraru; Jean-Eudes Petit; Florence Lafouge; Pauline Buysse; Sandy Bsaibes; Ben Henderson; Simona M. Cristescu; Brigitte Durand; Oliver Fanucci; Francois Truong; et al. (Science of The Total Environment, 2023)

Whitening of fire opal: Transformation of silica in soils - Simon Gouzy; Benjamin Rondeau; Pierre Gaudin; Guy Louarn; Carole La; Thierry Lebeau; Vassilissa Vinogradoff; Laura Clodoré; Sarah Chamard-Bois (Chemical Geology, 2023)

The fall of the summer truffle: Recurring hot, dry summers result in declining fruitbody production of Tuber aestivum in Central Europe - Brian S. Steidinger; Ulf Büntgen; Uli Stobbe; Willy Tegel; Ludger Sproll; Matthias Haeni; Barbara Moser; István Bagi; José‐Antonio Bonet; Marc Buée; Benjamin Dauphin; Fernando Martínez‐Peña; et al. (Global Change Biology, 2022)
Global warming is pushing populations outside their range of physiological tolerance. According to the environmental envelope framework, the most vulnerable populations occur near the climatic edge of their species' distributions. In contrast, populations from the climatic center of the species range should be relatively buffered against climate warming. We tested this latter prediction using a combination of linear mixed effects and machine learning algorithms on an extensive, citizen‐scientist generated dataset on the fruitbody productivity of the Burgundy (aka summer) truffle ( Tuber aestivum Vittad . ), a keystone, ectomycorrhizal tree‐symbiont occurring on a wide range of temperate climates. T. aestivum 's fruitbody productivity was monitored at 3‐week resolution over up to 8 continuous years at 20 sites distributed in the climatic center of its European distribution in southwest Germany and Switzerland. We found that T. aestivum fruitbody production is more sensitive to summer drought than would be expected from the breadth of its species' climatic niche. The monitored populations occurring nearly 5°C colder than the edge of their species' climatic distribution. However, interannual fruitbody productivity (truffle mass year −1 ) fell by a median loss of 22% for every 1°C increase in summer temperature over a site's 30‐year mean. Among the most productive monitored populations, the temperature sensitivity was even higher, with single summer temperature anomalies of 3°C sufficient to stop fruitbody production altogether. Interannual truffle productivity was also related to the phenology of host trees, with ~22 g less truffle mass for each 1‐day reduction in the length of the tree growing season. Increasing summer drought extremes are therefore likely to reduce fruiting among summer truffle populations throughout Central Europe. Our results suggest that European T. aestivum may be a mosaic of vulnerable populations, sensitive to climate‐driven declines at lower thresholds than implied by its species distribution model.

Dynamics of initial carbon allocation after drought release in mature Norway spruce—Increased belowground allocation of current photoassimilates covers only half of the carbon used for fine‐root growth - Kyohsuke Hikino; Jasmin Danzberger; Vincent P. Riedel; Benjamin D. Hesse; Benjamin D. Hafner; Timo Gebhardt; Romy Rehschuh; Nadine K. Ruehr; Melanie Brunn; Taryn L. Bauerle; Simon M. Landhäusser; Marco M. Lehmann; et al. (Global Change Biology, 2022)
After drought events, tree recovery depends on sufficient carbon (C) allocation to the sink organs. The present study aimed to elucidate dynamics of tree‐level C sink activity and allocation of recent photoassimilates (C new ) and stored C in c. 70‐year‐old Norway spruce ( Picea abies ) trees during a 4‐week period after drought release. We conducted a continuous, whole‐tree 13 C labeling in parallel with controlled watering after 5 years of experimental summer drought. The fate of C new to growth and CO 2 efflux was tracked along branches, stems, coarse‐ and fine roots, ectomycorrhizae and root exudates to soil CO 2 efflux after drought release. Compared with control trees, drought recovering trees showed an overall 6% lower C sink activity and 19% less allocation of C new to aboveground sinks, indicating a low priority for aboveground sinks during recovery. In contrast, fine‐root growth in recovering trees was seven times greater than that of controls. However, only half of the C used for new fine‐root growth was comprised of C new while the other half was supplied by stored C. For drought recovery of mature spruce trees, in addition to C new , stored C appears to be critical for the regeneration of the fine‐root system and the associated water uptake capacity.

Hidden fairy rings and males—Genetic patterns of natural Burgundy truffle ( Tuber aestivum Vittad.) populations reveal new insights into its life cycle - Florian Staubli; Lea Imola; Benjamin Dauphin; Virginie Molinier; Stephanie Pfister; Yasmine Piñuela; Laura Schürz; Ludger Sproll; Brian S. Steidinger; Uli Stobbe; Willy Tegel; Ulf Büntgen; et al. (Environmental Microbiology, 2022)
Burgundy truffles are heterothallic ascomycetes that grow in symbiosis with trees. Despite their esteemed belowground fruitbodies, the species' complex lifecycle is still not fully understood. Here, we present the genetic patterns in three natural Burgundy truffle populations based on genotyped fruitbodies, ascospore extracts and ectomycorrhizal root tips using microsatellites and the mating‐type locus. Distinct genetic structures with high relatedness in close vicinity were found for females (forming the fruitbodies) and males (fertilizing partner as inferred from ascospore extracts), with high genotypic diversity and annual turnover of males, suggesting that ephemeral male mating partners are germinating ascospores from decaying fruitbodies. The presence of hermaphrodites and the interannual persistence of a few males suggest that persistent mycelia may sporadically also act as males. Only female or hermaphroditic individuals were detected on root tips. At one site, fruitbodies grew in a fairy ring formed by a large female individual that showed an outward growth rate of 30 cm per year, with the mycelium decaying within the ring and being fertilized by over 50 male individuals. While fairy ring structures have never been shown for truffles, the genetics of Burgundy truffle populations support a similar reproductive biology as those of other highly prized truffles.

Mercury Exposure in Artisanal Mining: Assessing the Effect of Occupational Activities on Blood Mercury Levels Among Artisanal and Small-Scale Goldminers in Ghana - Benjamin M. Saalidong; Simon Appah Aram (Biological Trace Element Research, 2022)

DNA barcoding of traded shark fins in Peninsular Malaysia - Ying Giat Seah; Caroline Kibat; Simon Hew; Benjamin J. Wainwright (Reviews in Fish Biology and Fisheries, 2022)

Obesity: a perfect storm for carcinogenesis - Benjamin H. L. Harris; Valentine M. Macaulay; David A. Harris; Paul Klenerman; Fredrik Karpe; Simon R. Lord; Adrian L. Harris; Francesca M. Buffa (Cancer and Metastasis Reviews, 2022)
Obesity-related cancers account for 40% of the cancer cases observed in the USA and obesity is overtaking smoking as the most widespread modifiable risk factor for carcinogenesis. Here, we use the hallmarks of cancer framework to delineate how obesity might influence the carcinogenic hallmarks in somatic cells. We discuss the effects of obesity on (a) sustaining proliferative signaling; (b) evading growth suppressors; (c) resisting cell death; (d) enabling replicative immortality; (e) inducing angiogenesis; (f) activating invasion and metastasis; (g) reprogramming energy metabolism; and (h) avoiding immune destruction, together with its effects on genome instability and tumour-promoting inflammation. We present the current understanding and controversies in this evolving field, and highlight some areas in need of further cross-disciplinary focus. For instance, the relative importance of the many potentially causative obesity-related factors is unclear for each type of malignancy. Even within a single tumour type, it is currently unknown whether one obesity-related factor consistently plays a predominant role, or if this varies between patients or, even in a single patient with time. Clarifying how the hallmarks are affected by obesity may lead to novel prevention and treatment strategies for the increasingly obese population.

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Characterisation of carapace composition in developing and adult ostracods (Skogsbergia lerneri) and its potential for biomaterials - Benjamin M. Rumney; Siân R. Morgan; J. Frederick W. Mosselmans; F. Tegwen Malik; Simon J. Holden; Andrew R. Parker; Nick White; Philip N. Lewis; Julie Albon; Keith M. Meek (Marine Biology, 2022)
The protective carapace of Skogsbergia lerneri, a marine ostracod, is scratch-resistant and transparent. The compositional and structural organisation of the carapace that underlies these properties is unknown. In this study, we aimed to quantify and determine the distribution of chemical elements and chitin within the carapace of adult ostracods, as well as at different stages of ostracod development, to gain insight into its composition. Elemental analyses included X-ray absorption near-edge structure, X-ray fluorescence and X-ray diffraction. Nonlinear microscopy and spectral imaging were performed to determine chitin distribution within the carapace. High levels of calcium (20.3%) and substantial levels of magnesium (1.89%) were identified throughout development. Amorphous calcium carbonate (ACC) was detected in carapaces of all developmental stages, with the polymorph, aragonite, identified in A-1 and adult carapaces. Novel chitin-derived second harmonic generation signals (430/5 nm) were detected. Quantification of relative chitin content within the developing and adult carapaces identified negligible differences in chitin content between developmental stages and adult carapaces, except for the lower chitin contribution in A-2 (66.8 ± 7.6%) compared to A-5 (85.5 ± 10%) ( p = 0.03). Skogsbergia lerneri carapace calcium carbonate composition was distinct to other myodocopid ostracods. These calcium polymorphs and ACC are described in other biological transparent materials, and with the consistent chitin distribution throughout S. lerneri development, may imply a biological adaptation to preserve carapace physical properties. Realisation of S. lerneri carapace synthesis and structural organisation will enable exploitation to manufacture biomaterials and biomimetics with huge potential in industrial and military applications.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Distinct lineages and population genomic structure of the coral Pachyseris speciosa in the small equatorial reef system of Singapore - Bar Feldman; Lutfi Afiq-Rosli; Noa Simon-Blecher; Elena Bollati; Benjamin John Wainwright; Pim Bongaerts; Danwei Huang; Oren Levy (Coral Reefs, 2022)

The ultrastructural development and 3D reconstruction of the transparent carapace of the ostracod Skogsbergia lerneri - Benjamin M. Rumney; F. Tegwen Malik; Siân R. Morgan; Andrew R. Parker; Simon Holden; Julie Albon; Philip N. Lewis; Keith M. Meek (Marine Biology, 2022)
The Skogsbergia lerneri is a marine ostracod which possesses a carapace that is both protective and transparent. Since development of this carapace and how it is maintained in the adult is not known, the aim of this investigation was to carry out an in-depth ultrastructural study of the ostracod carapace at different developmental stages. Standard transmission electron microscopy and novel serial block face scanning electron microscopy (SBF-SEM) were undertaken to discern carapace ultrastructure in both two and three dimensions. Analysis revealed a carapace consisting of the same basic layer structure as other myodocopid ostracods, namely an epicuticle, exocuticle, endocuticle and membranous layer, but with a thinner adult carapace of mean thickness of 19.2 ± 1.78 µm, n = 5. The carapace layers, except for instar 1 ostracods, had similar relative proportions throughout development. The endocuticle and membranous layer thickened through advancing developmental stages due to an increase in calcified crystalline polyhedrons and a greater number of chitinous lamellae in the membranous layer. Crystalline polyhedron dimensions were significantly smaller near the boundary with the membranous layer. The borders between the carapace layers were indistinct; SBF-SEM revealed an abundance of epicuticle projections into the exocuticle and apparent gradual merging at the boundary of the exocuticle and the endocuticle. Here, we discuss how the S. lerneri carapace layer structure has evolved to serve a specific mechanical function, allowing surface protection and rigidity. In addition, we suggest that the lack of pigment and graduated layer boundaries contribute to the transparency of the carapace.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Characterizing the landscape compositions of urban wildlife encounters: the case of the stone marten (Martes foina), the red fox (Vulpes vulpes) and the hedgehog (Erinaceus europaeus) in the Greater Paris area - Mary Capon; Benjamin Lysaniuk; Vincent Godard; Céline Clauzel; Laurent Simon (Urban Ecosystems, 2021)

The Intersection of Parkinson’s Disease, Viral Infections, and COVID-19 - Benjamin Rosen; Alberim Kurtishi; Gonzalo R. Vazquez-Jimenez; Simon Geir Møller (Molecular Neurobiology, 2021)

The ID NOW COVID-19, a high-speed high-performance assay - Eric Farfour; M. Asso-Bonnet; M. Vasse; Emilie Catherinot; Colas Tcherakian; Antoine Magnan; Simon Chauveau; Sylvie Colin de Verdière; Hélène Salvatore; Antoine Roux; Benjamin Zuber; Charles Cerf; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Small freshwater ecosystems with dissimilar microbial communities exhibit similar temporal patterns - Gwendoline M. David; Purificación López‐García; David Moreira; Benjamin Alric; Philippe Deschamps; Paola Bertolino; Gwendal Restoux; Emma Rochelle‐Newall; Elisa Thébault; Marianne Simon; Ludwig Jardillier (Molecular Ecology, 2021)
Despite small freshwater ecosystems being biodiversity reservoirs and contributing significantly to greenhouse fluxes, their microbial communities remain largely understudied. Yet, microorganisms intervene in biogeochemical cycling and impact water quality. Because of their small size, these ecosystems are in principle more sensitive to disturbances, seasonal variation and pluri‐annual climate change. However, how microbial community composition varies over space and time, and whether archaeal, bacterial and microbial eukaryote communities behave similarly remain unanswered. Here, we aim to unravel the composition and intra/interannual temporal dynamic patterns for archaea, bacteria and microbial eukaryotes in a set of small freshwater ecosystems. We monitored archaeal and bacterial community composition during 24 consecutive months in four ponds and one brook from northwestern France by 16S rRNA gene amplicon sequencing (microbial eukaryotes were previously investigated for the same systems). Unexpectedly for oxic environments, bacterial Candidate Phyla Radiation (CPR) were highly diverse and locally abundant. Our results suggest that microbial community structure is mainly driven by environmental conditions acting over space (ecosystems) and time (seasons). A low proportion of operational taxonomic units (OTUs) (

Population pharmacokinetics of lopinavir/ritonavir in Covid-19 patients - Jean Claude Alvarez; Pierre Moine; Benjamin Davido; Isabelle Etting; Djillali Annane; Islam Amine Larabi; Nicolas Simon (European Journal of Clinical Pharmacology, 2021)

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

Spatiotemporal variations in eruption style and magnitude at Yasur volcano, Vanuatu: part 2—extending Strombolian eruption classifications - Benjamin Clifford Simons; S. J. Cronin; J. D. Eccles; A. D. Jolly; E. Garaebiti; S. Cevuard (Bulletin of Volcanology, 2020)

Establishment of long-term ostracod epidermal culture - Siân R. Morgan; Laura Paletto; Benjamin Rumney; Farhana T. Malik; Nick White; Philip N. Lewis; Andrew R. Parker; Simon Holden; Keith M. Meek; Julie Albon (In Vitro Cellular & Developmental Biology - Animal, 2020)
Primary crustacean cell culture was introduced in the 1960s, but to date limited cell lines have been established. Skogsbergia lerneri is a myodocopid ostracod, which has a body enclosed within a thin, durable, transparent bivalved carapace, through which the eye can see. The epidermal layer lines the inner surface of the carapace and is responsible for carapace synthesis. The purpose of the present study was to develop an in vitro epidermal tissue and cell culture method for S. lerneri . First, an optimal environment for the viability of this epidermal tissue was ascertained, while maintaining its cell proliferative capacity. Next, a microdissection technique to remove the epidermal layer for explant culture was established and finally, a cell dissociation method for epidermal cell culture was determined. Maintenance of sterility, cell viability and proliferation were key throughout these processes. This novel approach for viable S. lerneri epidermal tissue and cell culture augments our understanding of crustacean cell biology and the complex biosynthesis of the ostracod carapace. In addition, these techniques have great potential in the fields of biomaterial manufacture, the military and fisheries, for example, in vitro toxicity testing.

Blue Restoration – Building Confidence and Overcoming Barriers - Phoebe J. Stewart-Sinclair; Jemma Purandare; Elisa Bayraktarov; Nathan Waltham; Simon Reeves; John Statton; Elizabeth A. Sinclair; Benjamin M. Brown; Zoë I. Shribman; Catherine E. Lovelock (Frontiers in Marine Science, 2020)

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

Methods for coherent optical Doppler orbitography - Benjamin P. Dix-Matthews; Sascha W. Schediwy; David R. Gozzard; Simon Driver; Karl Ulrich Schreiber; Randall Carman; Michael Tobar (Journal of Geodesy, 2020)

Who is eating fructose within the Aedes albopictus gut microbiota? - Morgane Guégan; Van Tran Van; Edwige Martin; Guillaume Minard; Florence‐Hélène Tran; Benjamin Fel; Anne‐Emmanuelle Hay; Laurent Simon; Mohamed Barakat; Patrick Potier; Feth el Zahar Haichar; Claire Valiente Moro (Environmental Microbiology, 2020)
Summary The Asian tiger mosquito Aedes albopictus is a major public health concern because of its invasive success and its ability to transmit pathogens. Given the low availability of treatments against mosquito‐borne diseases, vector control remains the most suitable strategy. The methods used thus far are becoming less effective, but recent strategies have emerged from the study of mosquito‐associated microorganisms. Although the role of the microbiota in insect biology does not require further proof, much remains to be deciphered in mosquitoes, especially the contribution of the microbiota to host nutrient metabolism. Mosquitoes feed on plant nectar, composed of mostly fructose. We used stable isotope probing to identify bacteria and fungi assimilating fructose within the gut of Ae. albopictus . Mosquitoes were fed a 13 C‐labelled fructose solution for 24 h. Differences in the active microbial community according to the sex of mosquitoes were highlighted. The bacterium Lelliottia and the fungi Cladosporium and Aspergillus dominated the active microbiota in males, whereas the bacterium Ampullimonas and the yeast Cyberlindnera were the most active in females. This study is the first to investigate trophic interactions between Ae. albopictus and its microbiota, thus underscoring the importance of the microbial component in nectar feeding in mosquitoes.

Phreatomagmatic vs magmatic eruptive styles in maar-diatremes: a case study at Twin Peaks, Hopi Buttes volcanic field, Navajo Nation, Arizona - Benjamin Latutrie; Pierre-Simon Ross (Bulletin of Volcanology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The Role of Neuronal NLRP1 Inflammasome in Alzheimer’s Disease: Bringing Neurons into the Neuroinflammation Game - Jeremy Kean Yi Yap; Benjamin Simon Pickard; Elaine Wan Ling Chan; Sook Yee Gan (Molecular Neurobiology, 2019)

A macroinvertebrate multi-metric index for Ethiopian highland streams - Temesgen Alemneh; Argaw Ambelu; Benjamin F. Zaitchik; Simon Bahrndorff; Seid Tiku Mereta; Cino Pertoldi (Hydrobiologia, 2019)

Dopamine D2-like receptor stimulation blocks negative feedback in visual and spatial reversal learning in the rat: behavioural and computational evidence - Johan Alsiö; Benjamin U. Phillips; Júlia Sala-Bayo; Simon R. O. Nilsson; Teresa C. Calafat-Pla; Arazo Rizwand; Jessica M. Plumbridge; Laura López-Cruz; Jeffrey W. Dalley; Rudolf N. Cardinal; Adam C. Mar; Trevor W. Robbins (Psychopharmacology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Cellular Proteostasis in Neurodegeneration - Alberim Kurtishi; Benjamin Rosen; Ketan S. Patil; Guido W. Alves; Simon G. Møller (Molecular Neurobiology, 2019)

Höchstmögliche räumlich-zeitliche Auflösung in der Lichtmikroskopie - Simon Dersch; Benjamin Mayer; Daniel A. O. Rotter; Luis M. Oviedo-Bocanegra; Peter L. Graumann (BIOspektrum, 2019)

Habitat conservation banking trends in the United States - Jagdish Poudel; Daowei Zhang; Benjamin Simon (Biodiversity and Conservation, 2019)

Uncertainty associated with ambient ozone metrics in epidemiologic studies and risk assessments - Benjamin Wells; Heather Simon; Thomas J. Luben; Zachary Pekar; Scott M. Jenkins (Air Quality, Atmosphere & Health, 2019)

Transition zone between the upper diatreme and lower diatreme: origin and significance at Round Butte, Hopi Buttes volcanic field, Navajo Nation, Arizona - Benjamin Latutrie; Pierre-Simon Ross (Bulletin of Volcanology, 2019)

A domain-general brain network underlying emotional and cognitive interference processing: evidence from coordinate-based and functional connectivity meta-analyses - Taolin Chen; Benjamin Becker; Julia Camilleri; Li Wang; Shuqi Yu; Simon B. Eickhoff; Chunliang Feng (Brain Structure and Function, 2018)

Selective effects of 5-HT2C receptor modulation on performance of a novel valence-probe visual discrimination task and probabilistic reversal learning in mice - Benjamin U. Phillips; Sigma Dewan; Simon R. O. Nilsson; Trevor W. Robbins; Christopher J. Heath; Lisa M. Saksida; Timothy J. Bussey; Johan Alsiö (Psychopharmacology, 2018)

Annual Phytoplankton Primary Production Estimation in a Temperate Estuary by Coupling PAM and Carbon Incorporation Methods - Jérôme Morelle; Mathilde Schapira; Francis Orvain; Philippe Riou; Pascal Jean Lopez; Olivier Pierre-Duplessix; Emilie Rabiller; Frank Maheux; Benjamin Simon; Pascal Claquin (Estuaries and Coasts, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Quality‐assured long‐term satellite‐based leaf area index product - Jian Peng; Simon Blessing; Ralf Giering; Benjamin Müller; Nadine Gobron; Joanne Nightingale; Folkert Boersma; Jan‐Peter Muller (Global Change Biology, 2017)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Testing the usefulness of hydrogen and compound-specific stable isotope analyses in seabird feathers: a case study in two sympatric Antarctic storm-petrels - Petra Quillfeldt; Simon Thorn; Benjamin Richter; Marcela Nabte; Nestor Coria; Juan F. Masello; Melanie Massaro; Verónica C. Neves; Marcela Libertelli (Marine Biology, 2017)

Probiotic Enterococcus faecalis Symbioflor® down regulates virulence genes of EHEC in vitro and decrease pathogenicity in a Caenorhabditis elegans model - Klaus Neuhaus; Marina C. Lamparter; Benjamin Zölch; Richard Landstorfer; Svenja Simon; Britta Spanier; Matthias A. Ehrmann; Rudi F. Vogel (Archives of Microbiology, 2017)

A Multiplatform Experiment to Unravel Meso- and Submesoscale Processes in an Intense Front (AlborEx) - Ananda Pascual; Simon Ruiz; Antonio Olita; Charles Troupin; Mariona Claret; Benjamin Casas; Baptiste Mourre; Pierre-Marie Poulain; Antonio Tovar-Sanchez; Arthur Capet; Evan Mason; John T. Allen; et al. (Frontiers in Marine Science, 2017)

Where Does River Runoff Matter for Coastal Marine Conservation? - Alexa Fredston-Hermann; Christopher J. Brown; Simon Albert; Carissa J. Klein; Sangeeta Mangubhai; Joanna L. Nelson; Lida Teneva; Amelia Wenger; Steven D. Gaines; Benjamin S. Halpern (Frontiers in Marine Science, 2016)

Dynamic habitat corridors for marine predators; intensive use of a coastal channel by harbour seals is modulated by tidal currents - Gordon D. Hastie; Deborah J.F. Russell; Steven Benjamins; Simon Moss; Ben Wilson; Dave Thompson (Behavioral Ecology and Sociobiology, 2016)

Dwelling in the biosphere: exploring an embodied human–environment connection in resilience thinking - Benjamin Cooke; Simon West; Wiebren J. Boonstra (Sustainability Science, 2016)

The Role of Holocene Relative Sea-Level Change in Preserving Records of Subduction Zone Earthquakes - Tina Dura; Simon E. Engelhart; Matteo Vacchi; Benjamin P. Horton; Robert E. Kopp; W. Richard Peltier; Sarah Bradley (Current Climate Change Reports, 2016)

The social benefits of private infectious disease-risk mitigation - Benjamin R. Morin; Charles Perrings; Ann Kinzig; Simon Levin (Theoretical Ecology, 2015)

Elucidating the spatio‐temporal dynamics of an emerging wildlife pathogen using approximate Bayesian computation - Olivier Rey; Lisa Fourtune; Ivan Paz‐Vinas; Géraldine Loot; Charlotte Veyssière; Benjamin Roche; Simon Blanchet (Molecular Ecology, 2015)
Emerging pathogens constitute a severe threat for human health and biodiversity. Determining the status (native or non‐native) of emerging pathogens, and tracing back their spatio‐temporal dynamics, is crucial to understand the eco‐evolutionary factors promoting their emergence, to control their spread and mitigate their impacts. However, tracing back the spatio‐temporal dynamics of emerging wildlife pathogens is challenging because (i) they are often neglected until they become sufficiently abundant and pose socio‐economical concerns and (ii) their geographical range is often little known. Here, we combined classical population genetics tools and approximate Bayesian computation (i.e. ABC ) to retrace the dynamics of Tracheliastes polycolpus, a poorly documented pathogenic ectoparasite emerging in Western Europe that threatens several freshwater fish species. Our results strongly suggest that populations of T. polycolpus in France emerged from individuals originating from a unique genetic pool that were most likely introduced in the 1920s in central France. From this initial population, three waves of colonization occurred into peripheral watersheds within the next two decades. We further demonstrated that populations remained at low densities, and hence undetectable, during 10 years before a major demographic expansion occurred, and before its official detection in France. These findings corroborate and expand the few historical records available for this emerging pathogen. More generally, our study demonstrates how ABC can be used to determine the status, reconstruct the colonization history and infer key evolutionary parameters of emerging wildlife pathogens with low data availability, and for which samples from the putative native area are inaccessible.

Skeletal muscle proteomic signature and metabolic impairment in pulmonary hypertension - Simon Malenfant; François Potus; Frédéric Fournier; Sandra Breuils-Bonnet; Aude Pflieger; Sylvie Bourassa; Ève Tremblay; Benjamin Nehmé; Arnaud Droit; Sébastien Bonnet; Steeve Provencher (Journal of Molecular Medicine, 2015)

STDP in lateral connections creates category-based perceptual cycles for invariance learning with multiple stimuli - Benjamin D. Evans; Simon M. Stringer (Biological Cybernetics, 2015)

Estimating tectonic uplift of the Cape Fear Arch (south‐eastern United States) using reconstructions of Holocene relative sea level - ORSON VAN DE PLASSCHE; ALEX J. WRIGHT; BENJAMIN P. HORTON; SIMON E. ENGELHART; ANDREW C. KEMP; DAVID MALLINSON; ROBERT E. KOPP (Journal of Quaternary Science, 2014)
We use relative sea‐level (RSL) reconstructions and a spatiotemporal statistical model to estimate the rate of uplift of the Cape Fear Arch, a Mesozoic structural high, during the last ∼4000 years. We reconstructed RSL using 12 radiocarbon‐dated samples of basal salt‐marsh sediment preserved at Elizabeth Creek Marsh on the Cape Fear River. The new data show that RSL rose by ∼3 m during the past ∼4.6 ka at an average rate of 0.67 ± 0.12 mm a −1 . RSL reconstructions from other sites in southern North Carolina (which have rates of 0.91 ± 0.10 to 0.84 ± 0.24 mm a −1 ) probably show ( P > 0.9) higher rates of regional RSL rise for the same period, while sites from northern South Carolina (which have rates of 0.72 ± 0.17 to 0.80 ± 0.21 mm a −1 ) probably ( P > 0.67) show the same. We attribute the differences between Elizabeth Creek Marsh and neighboring regions to uplift of the Cape Fear Arch, which we estimate to be 0.24 ± 0.15 mm a −1 . Uplift of the arch may be responsible for lower rates of 20 th century RSL rise recorded by the Wilmington tide gauge relative to rates measured elsewhere along the US mid‐Atlantic coast.

The Navy Global Environmental Model - Timothy Hogan; Ming Liu; James Ridout; Melinda Peng; Timothy Whitcomb; Benjamin Ruston; Carolyn Reynolds; Stephen Eckermann; Jon Moskaitis; Nancy Baker; John McCormack; Kevin Viner; et al. (Oceanography, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Gene–smoking interactions in multiple Rho-GTPase pathway genes in an early-onset coronary artery disease cohort - Cavin Ward-Caviness; Carol Haynes; Colette Blach; Elaine Dowdy; Simon G. Gregory; Svati H. Shah; Benjamin D. Horne; William E. Kraus; Elizabeth R. Hauser (Human Genetics, 2013)

Influence of tidal‐range change and sediment compaction on Holocene relative sea‐level change in New Jersey, USA - BENJAMIN P. HORTON; SIMON E. ENGELHART; DAVID F. HILL; ANDREW C. KEMP; DARIA NIKITINA; KENNETH G. MILLER; W. RICHARD PELTIER (Journal of Quaternary Science, 2013)
We investigated the effect of tidal‐range change and sediment compaction on reconstructions of Holocene relative sea level (RSL) in New Jersey, USA. We updated a published sea‐level database to generate 50 sea‐level index points and ten limiting dates that define continuously rising RSL in New Jersey during the Holocene. There is scatter among the index points, particularly those older than 7 ka. A numerical model estimated that paleotidal range was relatively constant during the mid and late Holocene, but rapidly increased between 9 and 8 ka, leading to an underestimation of RSL by ∼0.5 m. We adjusted the sea‐level index points using the paleotidal model prior to assessing the influence of compaction on organic samples with clastic deposits above and below (an intercalated sea‐level index point). We found a significant relationship ( p = 0.01) with the thickness of the overburden ( r = 0.85). We altered the altitude of intercalated index points using this simple stratigraphic relationship, which reduced vertical scatter in sea‐level reconstructions. We conclude that RSL rose at an average rate of 4 mm a −1 from 10 ka to 6 ka, 2 mm a −1 from 6 ka to 2 ka, and 1.3 mm a −1 from 2 ka to AD 1900. Copyright © 2013 John Wiley & Sons, Ltd.

Priority Actions for Sustainable Forest Management in the International Year of Forests - DOMINICK A. DELLASALA; JOHN M. FITZGERALD; BENGT‐GUNNAR JONSSON; JEFFREY A. MCNEELY; BENJAMIN DELALI DOVIE; MARTIN DIETERICH; PATRICIA MAJLUF; SIMON C. NEMTZOV; OWEN T. NEVIN; E. CHRISTIEN M. PARSONS; JAMES E.M. WATSON (Conservation Biology, 2012)

Application of stable carbon isotopes for reconstructing salt‐marsh floral zones and relative sea level, New Jersey, USA - Andrew C. Kemp; Christopher H. Vane; Benjamin P. Horton; Simon E. Engelhart; Daria Nikitina (Journal of Quaternary Science, 2012)
We investigated use of δ 13 C in bulk organic sediment to define the botanical origin of samples preserved in coastal sediment as a means to reconstruct relative sea level in New Jersey, USA. Modern transects at three sites demonstrated that low and high salt‐marsh floral zones dominated by C 4 species ( Spartina alterniflora and Spartina patens ) were associated with sediment δ 13 C values between −18.9‰ and −15.8‰ and occurred from mean tide level (MTL) to mean higher high water (MHHW). Brackish transitional settings vegetated by Phragmites australis with Iva fructescens and Typha sp. (C 3 species) and freshwater upland samples (C 3 species) were characterized by bulk sediment δ 13 C values of −27.0‰ to −22.0‰ and existed above MHHW. Parallel transects at one site suggested that intra‐site variability was not discernible. The utility of δ 13 C values for reconstructing relative sea level in New Jersey is limited by an inability to differentiate between brackish sediments related to sea level and freshwater upland samples. To facilitate this distinction in a 4.4 m core, we used a multi‐proxy approach (δ 13 C values with presence or absence of agglutinated foraminifera) to recognize indicative meanings for four sample types. Sediment with δ 13 C values greater than −18.9‰ was derived from a vegetated salt‐marsh and formed between MTL and MHHW. Sediment with δ 13 C values less than −22.0‰ and containing agglutinated foraminifera formed in a brackish transitional zone between MHHW and highest astronomical tide (HAT). This is the narrowest elevational range of the four sample types and most precise sea‐level indicator. Sediment with δ 13 C values less than −22.0‰ and lacking foraminifera can only constrain the upper bound of former sea level. Samples with intermediate values (−22.0‰ to −18.9‰) formed between MTL and HAT. Using these indicative meanings and radiocarbon dates, we suggest that a transition from brackish to salt‐marsh δ 13 C values recorded in the core took approximately 350 years (from 1800 to 1450 cal. a BP). Copyright © 2011 John Wiley & Sons, Ltd.

Characterization of full-length MHC class II sequences in Indonesian and Vietnamese cynomolgus macaques - Hannah M. Creager; Ericka A. Becker; Kelly K. Sandman; Julie A. Karl; Simon M. Lank; Benjamin N. Bimber; Roger W. Wiseman; Austin L Hughes; Shelby L. O’Connor; David H. O’Connor (Immunogenetics, 2011)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

HOLOCENE SEA-LEVEL CHANGES ALONG THE UNITED STATES’ ATLANTIC COAST - Simon Engelhart; Benjamin Horton; Andrew Kemp (Oceanography, 2011)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

Identification of novel MHC class I sequences in pig-tailed macaques by amplicon pyrosequencing and full-length cDNA cloning and sequencing - Claire E. O’Leary; Roger W. Wiseman; Julie A. Karl; Benjamin N. Bimber; Simon M. Lank; Jennifer J. Tuscher; David H. O’Connor (Immunogenetics, 2009)

DNA recognition properties of the LHX3b LIM homeodomain transcription factor - Benjamin C Yaden; Jesse J. Savage; Chad S. Hunter; Simon J. Rhodes (Molecular Biology Reports, 2005)